PENDIDIKAN ISLAM BERBASIS MULTIKULTURALISME - Muhamad Mustaqim; Hikmatul Mustaghfiroh (ADDIN, 2013)
ISLAMIC EDUCATION BASED ON MULTI-CULTURALISM . The goal of Islamic education is always in line with the objectives of Islam. The Mission of Islam as a mercy for the worlds, will be realized when the Muslims are able to apply the Islamic teaching properly. Islamic education is a media for Muslims to be able to embody the essence of his creation, as abid and khalifah in this world. On the other hand, the diversity of man is an inevitability of life is always there. Diversity, which in this context is often termed as multicultural, is often being the womb of the emergence of problems and social conflict between human being. This is where the function of the Islamic education plays its role in order to equip the students with multicultural attitudes and awareness.